Courtship-feeding in the 'First Dates' restaurant is highly predictive of a second date. (1st October 2019) - Hendrie, Colin; Shirley, Isolde
Abstract: Food consumption is a common activity for couples when on a date. Sharing food is rated as being indicative of positive/friendly relations. One person feeding another indicates a stronger, often romantic relationship. It has been suggested that this may represent 'courtship' feeding that signals sexual interest. This is a low frequency behaviour however and so, many studies have used a staged interactions approach. This does not however allow the 'courtship' nature of the feeding to be unequivocally determined as there are no measures of outcome. The present study was conducted in an attempt to address this using broadcast footage of 'First Dates' (Twenty Twenty TV), a restaurant-based TV reality show where couples that have met for the first time eat a meal together. 792 dinner dates were analysed over 143 episodes. Feeding behaviour, where one person fed another, was seen in 58 male/female couples (mean age females = 26.21 ± 0.58, mean age males = 28.75 ± 0.86). 49 similarly aged couples where no feeding behaviour was observed were used as controls. Data revealed that females acted as feeders more often than males (38/58, 65.5%), that dessert was the most commonly fed course (41/58, 70.7%), with chocolate being the most common component (22/41, 53.6%) and that nearly all couples where feeding had been observed stated in a post-meal interview that they would wish to go on a second date (54/58, 93.1%), as compared to less than half of couples that did not food share (21/49, 42.9%). It is concluded that feeding behaviour in the 'First Dates' restaurant is indeed courtship behaviour, and that this is highly predictive of those couples agreeing to a second date.